MICROBIAL LOAD AND BACTERIAL DIVERSITY ON FACEMASKS USED BY STUDENTS OF CALEB UNIVERSITY, IMOTA, LAGOS STATE, NIGERIA - Oda, Onoja; Mohammed, Aisha; Osayuwamen, Imasuen Michelle (FUDMA Journal of Sciences, 2026)
Facemasks are essential in limiting bacterial shedding from the mouth and nose, thereby reducing the spread of infectious agents. This study aimed to isolate and identify bacterial species present on used facemasks worn by students of Caleb University, Imota, Lagos State. Forty (40) used facemasks were collected and analyzed microbiologically using phenotypic and biochemical methods. Results indicated that the majority of isolates were gram-negative rods. Identified bacteria included Klebsiella pneumonia, Yersinia pestis, Salmonella enterica, Citrobacter werkmanii, Escherichia albertii, Staphylococcus aureus, Pseudomonas aeruginosa, Salmonella typhi, Staphylococcus saprophyticus, and Yersinia pseudotuberculosis, Citrobacter werkmanii (14%), while several species including Klebsiella pneumoniae and Salmonella typhi were frequent (4% each). A higher bacterial load was observed on facemasks used by female students compared to males. The primary source of contamination was identified as the students’ own body surfaces, including the face, nose, mouth, and hands. These findings underscore the importance of proper facemask hygiene and it is strongly recommended that students replace masks daily after each use to reduce microbial contamination and the risk of infection.